2008
DOI: 10.1111/j.1502-3885.2006.tb01149.x
|View full text |Cite
|
Sign up to set email alerts
|

The role of inter-specific, micro-habitat and climatic factors on the carbon isotope (δ13C) variability of a modern leaf assemblage from northern Scandinavia: implications for climate reconstruction

Abstract: BOREAS Loader, N. J. & Rundgren, M. 2006 (May): The role of inter-specific, micro-habitat and climatic factors on the carbon isotope (d 13 C) variability of a modern leaf assemblage from northern Scandinavia: implications for climate reconstruction. Boreas, Vol. 35, pp. 188 Á/201. Oslo. ISSN 0300-9483.To provide a basis for the interpretation of past climatic conditions from Quaternary leaf records, leaf carbon isotope (d 13 C) results are presented for 12 northern European dwarf-shrub, shrub and tree species … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…This result agrees with plant physiological models and the findings of Loisel et al . (), but runs counter to methane carbon‐source models (Basiliko et al ., ; Raghoebarsing et al ., ; Larmola et al ., ) and some larger‐scale (non‐ Sphagnum ) space‐for‐time transects where it is possible that uncharacterized factors or inter‐site differences may have contributed to the nature of the relationships observed (Ménot and Burns, ; Loader and Rundgren, ; Skrzypek et al ., ; Amesbury et al ., ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This result agrees with plant physiological models and the findings of Loisel et al . (), but runs counter to methane carbon‐source models (Basiliko et al ., ; Raghoebarsing et al ., ; Larmola et al ., ) and some larger‐scale (non‐ Sphagnum ) space‐for‐time transects where it is possible that uncharacterized factors or inter‐site differences may have contributed to the nature of the relationships observed (Ménot and Burns, ; Loader and Rundgren, ; Skrzypek et al ., ; Amesbury et al ., ).…”
Section: Resultsmentioning
confidence: 99%
“…This provides a range of plant responses across a very wide range of environmental conditions, as might be expected if a single site were monitored over many decades (e.g. Ménot and Burns, ; Ménot‐Combes et al ., ; Loader and Hemming, ; Loader and Rundgren, ; Skrzypek et al ., , ; Amesbury et al ., ).…”
Section: Introductionmentioning
confidence: 99%
“…Yet, the tree ring isotope archive is not a purely physical archive, but also reflects biological processes. Several studies have observed that the isotope variations in leaves and wood of trees depend on the ecological site conditions, both for carbon and oxygen isotope ratios [ Barbour et al , 2001; Loader and Rundgren , 2006; Wang and Yakir , 1995]. At dry sites, for instance, the carbon isotope ratio may provide more information on precipitation variations than at comparably wet sites, similar to what is known for tree ring width variations [ Leavitt and Long , 1989].…”
Section: Introductionmentioning
confidence: 99%